About the nanoporosity elimination above 800 degrees C in xerogels prepared from TEOS sono-hydrolysis - Vollet, D. R.; Donatti, D. A.; Ruiz, A. I.; da Silva, JSP (Wiley-Blackwell, 2003)
Small angle X-ray scattering measurements, bulk and skeleton density data and an in-situ study by dilatometric thermal analysis about the nanoporosity elimination above 800 degreesC in TEOS sonogels are presented. Apparently, two processes act during the nanoporosity elimination, which precedes the foaming phenomenon often observed in such systems. The first, with an activation energy of (3.9 +/- 0.4) x 10(2) kJ/mol and high frequency factor, is the controlling process of the most nanoporosity elimination at higher temperature. The value of this activation energy is compatible to that for viscous flux throughout densification process in typical silica-based materials. The second, with an activation energy of (49 +/- 5) kJ/mol and low frequency factor, seems to be the controlling process of the first and extremely slow nanoporosity elimination at low temperature.